2015
DOI: 10.5114/wo.2014.46236
|View full text |Cite
|
Sign up to set email alerts
|

Cancer treatment in pregnant women

Abstract: In general, strategies for the treatment of cancer in pregnancy should not differ significantly from the treatment regimens in non-pregnant women. However, this is difficult due to either the effects of anticancer drugs on the developing foetus or the possibility of long-term complications after the exposure to drugs and radiation.The decision about the introduction and continuation of treatment in the event of pregnancy should be preceded by a detailed analysis of the potential benefits and risks. There are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 76 publications
0
45
0
3
Order By: Relevance
“…In general, strategies for the treatment of cancer in pregnancy are not different from the treatment regimens in non-pregnant women [12]; however, a woman cancer survivor who wants children might concern about the effects of adjuvant chemotherapy on future fertility or on future offspring. Bedschi et al [13] reported that age of the patient and the type and dose of chemotherapy are the main factors determining the magnitude of the damage in the ovary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, strategies for the treatment of cancer in pregnancy are not different from the treatment regimens in non-pregnant women [12]; however, a woman cancer survivor who wants children might concern about the effects of adjuvant chemotherapy on future fertility or on future offspring. Bedschi et al [13] reported that age of the patient and the type and dose of chemotherapy are the main factors determining the magnitude of the damage in the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…As for gastric cancer, TS-1 (tegafur, gimeracil, oteracil potassium), which is used as the standard adjuvant chemotherapy for patient with gastric cancer in Japan [14], and CDDP (cisplatin) are classified intermediate and low gonadotoxic chemotherapy respectively. However, there are limited data on fertility after any type of chemotherapy, and these data are difficult to interpret strictly [12]. For these facts, oocytes or fertilized egg cryopreservation would be better for young women, who want to have children following treatment, before receiving adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…There are no data to suggest that pregnancy termination alters the biological behavior of the tumor or patient prognosis in the presence of appropriate antineoplastic therapy [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Podstawą rozpoznania jest badanie histologiczne, a ciąża nie stanowi przeciwwskazania do wykonania biopsji zajętego narządu, w tym biopsji węzła chłonnego i trepanobiopsji szpiku. Wykonanie zabiegu w znieczuleniu miejscowym jest bezpieczne w każdym okresie ciąży, natomiast pobranie materiału do badania histopatologicznego w znieczuleniu ogólnym jest bezpieczne po upływie I trymestru [26][27][28].…”
Section: Choroby Nowotworowe Układów Krwiotwórczego I Chłonnegounclassified
“…Hemodylucja, zmniejszone stężenia albumin, zwiększony klirens nerkowy i wątrobowy zmieniają metabolizm leków, szybkość ich wydalania oraz biodostępność [26,27].…”
Section: Choroby Nowotworowe Układów Krwiotwórczego I Chłonnegounclassified